2000
DOI: 10.1093/ndt/15.8.1140
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of rosmarinic acid on the proliferation of cultured murine mesangial cells

Abstract: Rosmarinic acid inhibits cytokine-induced mesangial cell proliferation and suppresses PDGF and c-myc mRNA expression in PDGF-stimulated mesangial cells. Rosmarinic acid in Labiatae herbs might be a promising agent to prevent mesangial cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 13 publications
2
32
0
3
Order By: Relevance
“…In vitro studies revealed that RA inhibits cytokine-induced murine mesangial cell proliferation, suggesting that this substance may be useful in preventing the progression of mesangioproliferative glomerulonephritis. 16) This result was later confirmed by in vivo experiments, using the experimental model of ATS-induced glomerulonephritis in rats. 17) Again, as in other cases, the dimer of caffeic acid showed a much more pronounced effect than monomeric caffeic acid.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…In vitro studies revealed that RA inhibits cytokine-induced murine mesangial cell proliferation, suggesting that this substance may be useful in preventing the progression of mesangioproliferative glomerulonephritis. 16) This result was later confirmed by in vivo experiments, using the experimental model of ATS-induced glomerulonephritis in rats. 17) Again, as in other cases, the dimer of caffeic acid showed a much more pronounced effect than monomeric caffeic acid.…”
mentioning
confidence: 75%
“…15,18) In both cases, the active substances have been determined to be polyphenols: RA in the case of P. frutescens and lithospermate B in the case of S. miltiorrhizae. [15][16][17][18] A detailed investigation of the phenolic compounds in E. sericeum callus and root cultures revealed that RA and rabdosiin are the predominant CAMs synthesized by these cultures. 19) Additionally, the cultures contained trace amounts of eritrichin, a new substance identified as a trimer of caffeic acid that most likely represents a rabdosiin biosynthetic precursor.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-gout, antiinflammatory and antioxidant activity of celery extracts may be due to the presence of phenolic compounds, long chain fatty acids and phytosterols as reported by Mohamed and Al-okbi (2008). Sweet basil contains rosmarinic acid, which possesses anti-inflammatory and antioxidant activities (Makino et al, 2000;Jayasinghe et al, 2003). Sage leaf aqueous and butanol extracts have analgesic and anti-inflammatory effects due to the presence of carnosol and carnosic acid, which are phenolic diterpenes (Qnais et al, 2010;Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Its use since ancient times in traditional medicine is justiied by its antiseptic [1,2], antirheumatic [3], anti-inlammatory, antispasmodic [4,5], antimicrobial, and anti-hepatotoxic properties [6]. Its appreciation as a spice for seasoning and food preservation [7] is supported by a very high antioxidant activity [8].…”
Section: Introductionmentioning
confidence: 99%